Diagnostic utility of fine needle aspiration cytology in salivary gland lesions: a teaching institutional experience - Shetty, Shilpa M.; K. N., Kusuma (International Surgery Journal, 2019)
Background: Fine needle aspiration cytology (FNAC) is being widely used for pre-operative diagnosis of salivary gland lesions. It is a simple, cost effective and safe procedure that provides valuable information for planning appropriate management. The aim was to study cytohistopathological correlation of salivary gland lesions; to examine sensitivity, specificity and diagnostic accuracy of fine needle aspiration cytology of salivary gland lesions. Methods: A 4 year 8 months study was conducted from January 2015 to August 2019. Salivary gland lesion FNAC performed in the Department of Pathology, SIMS, Shimoga who were followed up with corresponding biopsy specimen were included in the study. Results: Total of 42 cases was included in the study. Pleomorphic adenoma was the commonest lesion encountered. The overall sensitivity, specificity, diagnostic accuracy, positive predictive value and negative predictive value was 50%, 97.22%, 90.47%, 75% and 92.10%. Diagnostic pit falls occurred because of sampling error and overlapping morphological features. Conclusions: Fine needle aspiration (FNA) though poses diagnostic dilemma in some cases, it still forms an easy and less invasive procedure that can assess therapeutic management of salivary gland lesions.